The relationship of skin autofluorescence with diastolic function and HFA-PEFF score in a general population of older people - Teren, Marian; Schott, Artjom; Sedding, Daniel; Nuding, Sebastian; Simm, Andreas; Großkopf, Anne; Greiser, Karin Halina; Kluttig, Alexander; Mikolajczyk, Rafael (Nutrition, metabolism and cardiovascular diseases, 2022)
advanced glycation end-products, skin autofluorescence, diastolic function, heart failure, HFA-PEFF, older persons, elderly